Identification and Pathogenic Potential of Clinical Bacillus and Paenibacillus Isolates - Celandroni, Francesco (PLoS One, 2016)
The soil-related Bacillus and Paenibacillus species have increasingly been implicated in various human diseases. Nevertheless, their identification still poses problems in the clinical microbiology laboratory and, with the exception of Bacillus anthracis and Bacillus cereus, little is known on their pathogenicity for humans. In this study, we evaluated the use of matrix-assisted laser desorption—ionization time of flight mass spectrometry (MALDI-TOF MS) in the identification of clinical isolates of these genera and conducted genotypic and phenotypic analyses to highlight specific virulence properties. Seventy-five clinical isolates were subjected to biochemical and MALDI-TOF MS identification. 16S rDNA sequencing and supplemental tests were used to solve any discrepancies or failures in the identification results. MALDI-TOF MS significantly outperformed classical biochemical testing for correct species identification and no misidentification was obtained. One third of the collected strains belonged to the B. cereus species, but also Bacillus pumilus and Bacillus subtilis were isolated at high rate. Antimicrobial susceptibility testing showed that all the B. cereus, B. licheniformis, B. simplex, B. mycoides, Paenibacillus glucanolyticus and Paenibacillus lautus isolates are resistant to penicillin. The evaluation of toxin/enzyme secretion, toxin-encoding genes, motility, and biofilm formation revealed that B. cereus displays the highest virulence potential. However, although generally considered nonpathogenic, most of the other species were shown to swim, swarm, produce biofilms, and secrete proteases that can have a role in bacterial virulence. In conclusion, MALDI-TOF MS appears useful for fast and accurate identification of Bacillus and Paenibacillus strains whose virulence properties make them of increasing clinical relevance.